Deskripsi Kemampuan Berpikir Analitis Siswa Dalam Pembelajaran Matematika Pada Materi Operasi Bilangan Pecahan - Napui, Ismawanti; Takaendengan, Bertu Rianto; Resmawan, Resmawan; Pauweni, Khardiyawan A.Y (Universitas Pekalongan, 2024)
This study aims to describe students' analytical thinking skills in learning mathematics on fraction operations. This research was conducted at SMP Negeri 1 Ponelo Kepulauan which involved 26 students. This data collection technique is in the form of essay tests and interviews totaling 8 questions. To measure students' ability to think analytically, 3 indicators are used, namely: 1) Differentiating, 2) Organizing, and 3) Connecting. The results of this study indicate that students' analytical thinking skills in learning mathematics for class VII students of SMP Negeri 1 Ponelo Kepulauan are still in the moderate category because they reach a percentage of. Furthermore, the results for each indicator also belong to the medium category because it achieves a presentation of 61.54% respectively; 53.85%; 65.38%.